1993
DOI: 10.1902/jop.1993.64.4.302
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Restoration and Furcation Involvement on Molar Teeth

Abstract: The purpose of this cross-sectional study was to examine the correlation between the presence of a crown (CR) or a proximal restoration (RE) and furcation involvement (FI) on molar teeth. Data were collected from 134 periodontal maintenance patients who had restored and non-restored molars present both with and without FI. A majority of the restorations that were present in these patients had been in place for at least 5 years prior to the study. First and second molars were examined clinically using the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 7 publications
1
23
0
3
Order By: Relevance
“…Other studies 8 showed higher values of CAL in subgingivally located restorations, independently of the observed adaptation. Although showing higher values of CAL for crowned teeth, Wang et al 17 (1993) did not find statistically significant differences between crowned and sound teeth. The outstanding study of Schätzle et al 13 (2001), that evaluated 160 patients during 26 years, did not find statistically significant differences between the study groups, similarly to the results of the present study.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies 8 showed higher values of CAL in subgingivally located restorations, independently of the observed adaptation. Although showing higher values of CAL for crowned teeth, Wang et al 17 (1993) did not find statistically significant differences between crowned and sound teeth. The outstanding study of Schätzle et al 13 (2001), that evaluated 160 patients during 26 years, did not find statistically significant differences between the study groups, similarly to the results of the present study.…”
Section: Discussionmentioning
confidence: 89%
“…ARNEBERG et al 4 , perda de inserção 3,8,11,23 , reabsorção óssea e lesões de bifurcação 23 . Este processo patológico é decorrente do acúmulo de placa bacteriana em regiões onde o seu controle muitas vezes é impossível de ser realizado; bem como de alterações na microbiota periodontal 10 .…”
Section: Discussionunclassified
“…Clinically it could manifest as gingival bleeding and periodontal pocket formation. Histological and clinical investigations of periodontal tissues response to restorations with margins altering gingival biological width confirmed these statements [6][7][8][9][10][11][12][13][14]. It is established that minimal width of 2 mm is needed for gingiva to attach to the bone.…”
Section: Alterations Of Biological Widthmentioning
confidence: 95%